Ultraestructura de rotavirus - Hernández, Francisco (1986)
The human rotavirus is an icosadeltahedral structure, with a characteristic pattern of a triangulation number (T) of 13 with a skew symmetry. The inner layer of the rotavirus has 132 morphological units, with 260 structural units of trimetric sctructure. It is possible that the outer layer is a smooth geodesic shell.